Penyuluhan Kerjasama Tim sebagai Kunci Meraih Kemenangan pada Tim Futsal SMK Hang Tuah 1 Jakarta - Zulkarnaini Zulkarnaini; Bayu Pratama; Rutinaias Haholongan; Mochammad Alaudin; Dzakaa Naufal Fakhri (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Futsal is a sport that demands solid teamwork to achieve victory. However, at the vocational high school (SMK) level, many futsal teams still rely solely on individual skills without considering the importance of synergy and communication between players. This outreach activity aims to increase the understanding and awareness of the SMK Hang Tuah 1 Jakarta futsal team regarding the importance of good teamwork. The outreach method used in this outreach was interactive and game simulations that emphasized communication strategies, role-playing, and trust among team members. The results of this activity showed a significant improvement in team coordination and cohesiveness. Players also demonstrated a better understanding of their respective roles and were able to make collective decisions on the field. It is hoped that the results of this outreach will serve as a foundation for the SMK Hang Tuah 1 Jakarta futsal team to develop their potential and achieve even better results in the future.